2021
DOI: 10.3389/fmolb.2021.717328
|View full text |Cite
|
Sign up to set email alerts
|

Players in Mitochondrial Dynamics and Female Reproduction

Abstract: Mitochondrial dynamics (fission and fusion) are essential physiological processes for mitochondrial metabolic function, mitochondrial redistribution, and mitochondrial quality control. Various proteins are involved in regulating mitochondrial dynamics. Aberrant expression of these proteins interferes with mitochondrial dynamics and induces a range of diseases. Multiple therapeutic approaches have been developed to treat the related diseases in recent years, but their curative effects are limited. Meanwhile, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 182 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al also concluded that the release properties of PLGA NPs was not rendered by the low temperature ( Zhang et al, 2019 ). As central organelles for metabolism and ROS production, mitochondria supply large amounts of ATP during meiosis and exhibit organelle rearrangements during nuclear and cytoplasmic maturation through mtDNA replication and mitochondrial dynamics ( Udagawa and Ishihara, 2020 ; Zou et al, 2021 ). It has been shown that vitrification can significantly affect the function and distribution of mitochondria in oocytes ( Lei et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al also concluded that the release properties of PLGA NPs was not rendered by the low temperature ( Zhang et al, 2019 ). As central organelles for metabolism and ROS production, mitochondria supply large amounts of ATP during meiosis and exhibit organelle rearrangements during nuclear and cytoplasmic maturation through mtDNA replication and mitochondrial dynamics ( Udagawa and Ishihara, 2020 ; Zou et al, 2021 ). It has been shown that vitrification can significantly affect the function and distribution of mitochondria in oocytes ( Lei et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the function of mitochondria in porcine oocytes was studied. Mitochondrial dysfunction can destroy the female reproductive function of oocyte maturation, fertilization and embryonic development [45]. Strong evidence indicated that ZEA damaged Sertoli cells through reducing mitochondrial membrane potential and altering mitochondrial structure [46].…”
Section: Discussionmentioning
confidence: 99%